STRATEGI MENINGKATKAN MUTU PENDIDIKAN MELALUI PROGRAM KELAS EXCELLENT SMP PLUS DARUSSALAM BANYUWANGI - Nur Hidayati; Wandariatul Maghfiroh (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2021)
Improving the quality of education is one of the main pillars in building education in Indonesia, because if education is of good quality, it will produce intelligent and competitive human resources. In order to improve the quality of education it is necessary to organize one of them by providing educational program services that accommodate the needs of special students to optimize their potential. One of the forums for special students, one of which is the holding of an excellent class program. This study aims to determine the strategy in improving the quality of education through the excellent class program at SMP Plus Darussalam Blokagung Tegalsari Banyuwangi. The subject of this research is the principal, WKS. The curriculum and the head of the excellent class dormitory are Al-Aziziyyah. This research method uses descriptive qualitative, data collection methods through observation, interviews, documentation, archival records and physical devices. The validity of the data uses credibility, transferability, dependability, and confirmability. The data analysis used is SWOT analysis. From the results of this study, the strategies used in improving the quality of education through the excellent class program at SMP Plus Darussalam Blokagung Tegalsari Banyuwangi include: (1) There is a selective selection process, (2) Improving the quality of teachers, (3) The existence of a study club, (4) The existence of a special dormitory for superior students, (5) The existence of a mini library, and (6) Strengthening the plus value in the community both in terms of academic and non-academic.